Automating block caves: learning from the past - Mowen, J.; Millane, J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Load-haul-dump (LHD) automation can be a key control to minimising risk during mid- to late-stage block cave production where there is an increase in fines and elevated inrush risk. However, in early stages of design and implementation there is a clear tension between cave establishment, ramp-up, productivity and capital cost, and the installation and use of automation. Mobile fleet automation systems have been installed at several high-profile operations across the globe – despite this, block caving production remains predominantly manual, even those operations that have seen historical deployments of large-scale autonomous solutions. The impetus to transition to a remotely operated fleet has often been a result of operational needs – mature caves pose a heightened inrush risk to personnel and this increased risk becomes unacceptable over time. Even though some mines have promoted the productivity, efficiency or other safety benefits that may come with automation, the autonomous system is often implemented based on an ad hoc trigger late in the life of the cave. These mines are not set up to operate effectively using remote equipment and have an operational culture that is not prepared for, or even hostile to, the change in approach. Designing for eventual automation is crucial to the late stages of a block cave and should be examined in the early stages of study work. Establishing practices to prepare the operation for a transition to remote production is essential for a modern block cave. How this can be done well and how it has been unsuccessful are both critical learnings from past and active operations.